Faktor-Faktor Penyebab Pending Klaim BPJS Rawat Inap Di RSUD Dr. Pirngadi Kota Medan Tahun 2022 - Christy, Johanna; Nengsih, Yeyi Gusla; Sitorus, Mei Sryendang; Widyasari, Savira (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda (JIPIKI), 2024)
BPJS claims are submissions for patient care costs for BPJS participants in claiming that there are problems pending claims which are influenced by several factors. The implementation of BPJS claims in submitting files is still delayed so it must be pending, and there are still patient BPJS claim files that are returned for repair, as a result of delays in submitting BPJS claims causing delays in disbursing funds that should be received by the hospital. the factors that cause pending BPJS claims at RSUD Dr. Pirngadi Medan City. The purpose of this study was to determine the factors causing pending claims of BPJS Inpatients at RSUD Dr. Pirngadi Medan City in 2022. This type of research uses a qualitative descriptive method, in this study the population used by officers in the medical record amounted to 4 people and 49 pending files. The results of this study indicate that the cause of pending BPJS claims is caused by differences in perceptions between INA CBG's officers and Verifiers in filling out patient diagnoses, causing obstacles for hospitals, incomplete BPJS claim requirements, diagnoses that are not in accordance with the action, drugs that are not in accordance with diagnostics and the hospital network which is sometimes slow, resulting in errors in the INA-CBGs application and the computer takes a long time to load. Suggestions from this study should be routine checking of the completeness of medical record documents, so that the requirements for submitting BPJS claims have been filled out correctly. The hospital network is further developed so that the work using computer networks is more effective. To equate the perception between the coder and the verifier, it is recommended that officers collaborate more often with doctors regarding diagnosis and disease codes.